2002
DOI: 10.1063/1.1508428
|View full text |Cite
|
Sign up to set email alerts
|

Controlled group V intermixing in InGaAsP quantum well structures and its application to the fabrication of two section tunable lasers

Abstract: We report the technique of controlled group V quantum well intermixing (QWI) in a compressively strained In0.76Ga0.24As0.85P0.15/In0.76Ga0.24As0.52P0.48 multiquantum well laser structure and its application to the fabrication of two-section tunable lasers. The blueshift of the band-gap energy was enhanced by capping the samples with films of SiO2 or low-temperature grown InP, while suppressed by a SixNy film with a refractive index of about 2.1. Spatially selective band-gap tuning was achieved by patterning th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…6,8 From secondary ion mass spectroscopy (SIMS) measurements, it has been reported that on InP based QW structures, In and Ga atoms are easier to outdiffuse to the SiO 2-x layer and create V interstitials that enhance interdiffusion between barrier and well materials during RTA. 9 XPS depth profiling results also demonstrated that the total concentration of In and Ga atoms outdiffusing to the SiO 2 layer could be at around 0.5 at. % while a negligible presence of P atoms has been found in SiO 2 .…”
Section: Introductionmentioning
confidence: 93%
“…6,8 From secondary ion mass spectroscopy (SIMS) measurements, it has been reported that on InP based QW structures, In and Ga atoms are easier to outdiffuse to the SiO 2-x layer and create V interstitials that enhance interdiffusion between barrier and well materials during RTA. 9 XPS depth profiling results also demonstrated that the total concentration of In and Ga atoms outdiffusing to the SiO 2 layer could be at around 0.5 at. % while a negligible presence of P atoms has been found in SiO 2 .…”
Section: Introductionmentioning
confidence: 93%
“…Various methods have been studied to control the QW intermixing in GaAs and InPbased QW structures [14][15][16]. Among them, impurity-free vacancy-enhanced disordering (IFVD) has been proved to be a simple and effective method on InGaAs/GaAs QW intermixing with minor side effects on the crystal quality and optical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the intermixing mechanism on different material systems has been investigated and can be ascribed to the disordering of different atoms. It has been shown that the intermixing of group V atoms (As and P) is responsible for the bandgap shift in InGaAsP-based QW structures; 10 while the interdiffusion of In and Ga atoms can be found in intermixed GaInNAs/GaAs QW structures. 11 We have previously reported promoted and inhibited intermixing in AlInGaAs-based MQW laser structures by depositing SiN x and SiO 2 dielectric capping layers, respectively, followed by rapid thermal annealing (RTA), where the differential emission wavelength was measured to be more than 100 nm.…”
Section: Sin X -Induced Intermixing In Alingaas/inp Quantum Well Thromentioning
confidence: 99%
“…2,3 The process steps associated with the QWI are generally simple in comparison with the asymmetric twin-waveguide (ATG) 4 approach to PICs, where delicate taper designs are required to transfer light in the vertical plane or with the epitaxial regrowth approach where regrowth 5 with Al containing materials is difficult. Among the various intermixing methods, the top surface being encapsulated with a dielectric film prior to thermal annealing [6][7][8][9][10][11][12] is advantageous since it does not require sacrificial layers or external atoms and thus potential additional damage to the quantum well (QW) structure can be minimized. In this intermixing scenario, the creation and diffusion of vacancies created at the interface of the dielectric film and semiconductor top layer 6 are a prerequisite and those point defects may in turn cause the inbuilt strain within QW to be relaxed through the atomic interdiffusion.…”
Section: Sin X -Induced Intermixing In Alingaas/inp Quantum Well Thromentioning
confidence: 99%